Digital Leadership and AI Literacy Among Financial Technology Professionals: An Empirical Investigation of Relationships and Predictive Capabilities - Bulan, Jefferson; Co, Stephen Jay (Southeast Asian Business Review, 2025)
This research examined the association between digital leadership capabilities and artificial intelligence literacy among fintech professionals, examining how human-centric leadership dimensions correlate with AI competency components and their predictive relationships. A quantitative correlational design was employed with 76 financial technology professionals across diverse roles and organizations. Data collection employed the validated Digital Leadership Scale, which evaluates seven human-centered dimensions, along with the AI Literacy Scale that examines four essential components. Significant positive correlations were found between all digital leadership dimensions and AI literacy components, with an overall strong relationship between constructs. Operations managers showed the highest digital leadership levels while data engineers demonstrated superior AI literacy. Regression modeling demonstrated that digital leadership dimensions together accounted for 28.3% of the variance observed in AI literacy, though individual dimensions were non-significant due to multicollinearity, suggesting digital leadership functions as a holistic construct. Results indicate that comprehensive digital leadership development programs addressing multiple dimensions simultaneously may enhance AI literacy more effectively than isolated skill-building initiatives. The validated relationship between digital leadership and AI literacy provides evidence-based support for integrated leadership development strategies in technology-intensive environments, particularly benefiting fintech organizations navigating AI-driven transformation challenges.